FPGA Implementation of Wavelet Filters for DWMT Systems - I. Siddiq, Abdulrahman; M. Salih, Omar (Kirkuk Journal of Science, 2016)
Discrete Wavelet Multi-Tone (DWMT) systems acquired attention due to their high spectral efficiency and high data rates with respect to FFT-based multitone transmission systems. The complexity of the overall system is directly related to that of the elemental building block. In the literature, wavelet filters are designed subject to constraints for minimum interference. The structure of a Minimum Interference Wavelet Filter (MIWF) is very simple even for high filter orders. In this paper, DWMT systems using a two-branch wavelet filter bank in the transmitter and its inverse at the receiver are implemented using the Spartan XC3S1200E FPGA. The details of system implementation are presented for MIWF, Daubechies, and Coiflet wavelet filters. The tests show that, with respect to the other tested systems, the MIWF-based system is simpler, faster and capable to preserve its